The Effect of Effective Tax Rate and Tunneling Incentive on Transfer Pricing Decisions in Mining Companies Listed on the Indonesia Stock Exchange for the 2019-2021 Period - Ayuningtyas, Nikka; Budiantara, Martinus (PT FORMOSA CENDEKIA GLOBAL, 2024)
Companies in the mining industry make decisions to determine transfer pricing, the purpose of this study is to examine the role of effective tax rate (ETR) and tunneling incentives in transfer pricing. All companies listed on the IDX for the mining sector from 2019 to 2021 make up the population of this study. This study uses a quantitative method, which relies on numerical data. A total of 12 companies were sampled for this study, over 4 years. The analysis in this study found that neither the effective tax rate nor the tunnelling incentive had any influence on the decisions made regarding the determination of transfer pricing.